Association Between Components of a Self-management Theory and Falls Among Older Adults - (:unkn) unknown (My University, 2022)
Objectives: The purpose of this study was to examine self-management process factors, proximal outcomes, and distal outcomes of fall prevention utilizing the Individual Family and Self-Management Theory (IFSMT) in older adults residing in CCRC’s in a Midwest community. Design: This descriptive study was a secondary data analysis of a cross-sectional correlational study. Setting: Completed in six Continuing Care Retirement Communities in a Midwest state. Participants: Ninety-nine participants ranged in age from 70-99 years of age. Measurement: The data for self-efficacy, goal congruence, social support, aging expectation, protein intake, vitamin D intake, and total number of falls was obtained through questionnaires. The data for physical activity was retrieved from an Actigraph GT3X+ which the older adult wore for 7 days. Both logistic and multivariant statistics were used to analyze the data. Multicollinearity was assessed for each model. Results: Those participants with higher self-efficacy for physical activity exhibited more steps per day. Higher expectations regarding aging demonstrated a reduced likelihood of meeting daily protein intake. Meeting vitamin D intake was not associated with any of the variables. Falls were not associated with any of the process variables (self-efficacy, goal congruence, social support, and aging expectations). Further research is needed to better understand the results of this study, and to develop interventions to prevent falls as well as the negative health outcomes associated with falls in older adults. Conclusion: Further research is needed to determine what impacts these relationships and what interventions can prevent falls in older adults residing in continuing care retirement communities. There may be factors that affect older adults residing in CCRC’s that may not pertain to older adults living within the community. Self-management interventions that prevent falls in older adults has the potential to impact not only those who have fallen but those who have not yet experienced a fall. Further research is needed to develop and implement interventions to prevent falls as well as the negative health outcomes associated with falls in older adults.
Keywords: Fall; Individual and Family Self-Management Theory; Older adult; Prevention